Optimalisasi Edukasi Kesehatan Pemberian Tablet Fe sebagai bentuk upaya pencegahan Anemia pada Remaja SMA Negeri 4 Kota Sorong - Baktianita Ratna Etnis; Junaiddin Junaiddin; Yulinda Margaret Bambungan; Muhammad Faizal Arianto (Jurnal Inovasi, Pemberdayaan dan Pengabdian Masyarakat, 2022)
Anemia is a medical condition in which the number of red blood cells or hemoglobin is less than normal. The incidence of anemia in Indonesia is 21.7%. 18.4% occurred in males and 23.9% occurred in females. Based on the criteria for the age of 5-14 years it reached 26.4% and at the age of 15-25 years it reached 18.4%. Based on these data, community service activities are carried out with the aim of youth, which aims to provide knowledge by optimizing health education as an effort to prevent anemia in adolescents at SMAN 4 Sorong City so that adolescents can understand the dangers of anemia besides that adolescents can also apply how to consume good and correct Fe tablets as a form of optimizing the prevention of anemia in adolescents. The results obtained after the adolescents were given education about administering Fe tablets as a prevention of anemia, showed that there was an increase in the knowledge of 28 adolescents regarding the importance of preventing anemia by consuming Fe tablets properly and correctly.